The Case for a Core Anti-racist Course for Counselors in Training - Ileana A Gonzalez Ph.D.; Raven K Cokley Ph.D. (Teaching and Supervision in Counseling, 2021)
Historically, counseling programs in the United States have been rooted in whiteness and white supremacy. Despite this historical context, counseling programs fail to teach students about the varied ways that anti-Blackness and systemic racism show up in society, classrooms, and clinical settings. Given the systemic murders of Black folks by the state, the health disparities highlighted by the COVID-19 pandemic, and the refusal of white voters to abandon white supremacist patriarchy in the 2020 presidential election, the counseling field must reconsider how it prepares trainees to embrace anti-racism in their personal and professional lives. The purpose of this article is to propose a core anti-racist counseling course to assist students in developing an anti-racist counseling identity including pedagogical practices, course learning objectives and assignments. Implications will be provided for counselor preparation programs, counseling students, and counselor educators to employ.
Keywords: Anti-racist training; anti-racist counseling identity; counselor education